2016
DOI: 10.1111/mpp.12500
|View full text |Cite
|
Sign up to set email alerts
|

Host‐induced gene silencing compromises Verticillium wilt in tomato and Arabidopsis

Abstract: SUMMARYVerticillium wilt, caused by soil-borne fungi of the genus Verticillium, is an economically important disease that affects a wide range of host plants. Unfortunately, host resistance against Verticillium wilts is not available for many plant species, and the disease is notoriously difficult to combat. Host-induced gene silencing (HIGS) is an RNA interference (RNAi)-based process in which small RNAs are produced by the host plant to target parasite transcripts. HIGS has emerged as a promising strategy fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 69 publications
(117 reference statements)
1
63
0
Order By: Relevance
“…At ten days after TRV treatment, plants were challenged with either the V. dahliae race 1 strain JR2 , or an Ave1 deletion mutant (V. dahliae JR2△Ave1;, and inspected for Verticillium wilt symptoms (stunting and wilting) up to 14 days post inoculation (dpi). As expected, no significant disease symptoms were observed on TRV::GUStreated plants that were inoculated with the wild-type race 1 V. dahliae strain (Song et al, 2016 It was recently demonstrated that Tobacco mosaic virus (TMV) may infect fungi in addition to plants, remaining for up to six subcultures, and also persisted in plants infected by the virus-infected fungus (Mascia et al, 2014 Figure S1A). Furthermore, the fungal isolates were used to infect Ve1 tomato plants and tomato plants that lack…”
Section: Tobacco Rattle Virus (Trv)-based Virus-induced Gene Silencinmentioning
confidence: 85%
See 4 more Smart Citations
“…At ten days after TRV treatment, plants were challenged with either the V. dahliae race 1 strain JR2 , or an Ave1 deletion mutant (V. dahliae JR2△Ave1;, and inspected for Verticillium wilt symptoms (stunting and wilting) up to 14 days post inoculation (dpi). As expected, no significant disease symptoms were observed on TRV::GUStreated plants that were inoculated with the wild-type race 1 V. dahliae strain (Song et al, 2016 It was recently demonstrated that Tobacco mosaic virus (TMV) may infect fungi in addition to plants, remaining for up to six subcultures, and also persisted in plants infected by the virus-infected fungus (Mascia et al, 2014 Figure S1A). Furthermore, the fungal isolates were used to infect Ve1 tomato plants and tomato plants that lack…”
Section: Tobacco Rattle Virus (Trv)-based Virus-induced Gene Silencinmentioning
confidence: 85%
“…Constructs for the constitutive expression of VdAve1, SlPNP, VvPNP, FoAve1, CbAve1, ChAve1 and XacPNP have been described previously Song et al, 2016). VnAve1 was amplified from V.…”
Section: Methods S1 Generation Of Binary Expression Vectorsmentioning
confidence: 99%
See 3 more Smart Citations